Kerajaan Allah Dan Kehidupan Dalam Roh Prioritas Hidup Orang Percaya Menurut Roma 8:1-17 - Purwani, Asih; Yosef, Hery Budi (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2024)
Every believer is called to be a witness for Christ in this world. In carrying out this task, believers face situations that are not easy, there are challenges from within themselves and from outside themselves. Therefore, God has equipped believers with spiritual power, namely the Holy Spirit. God's action in Jesus Christ underlies the entire theological development of Paul and believers, in their existence in Christ, while allowing themselves to be led by the Holy Spirit, also participating in the status of children of God, the Holy Spirit then becomes the key point of people's new reality believe. The meaning of the kingdom of God is often discussed by God's servants who reveal that the kingdom of God is something that will come or is happening now. This article provides readers with an understanding that getting to know the Kingdom of God is a priority in the life of believers. The Kingdom of God can only be known, recognized, and obtained by knowing God in Christ as its foundation. This research uses an exegesis method with a word analysis approach from the original text, namely finding the spiritual meaning behind the original text. This article is the result of the discovery of four layers of exegetical meaning from Romans 8:1-17 and is supported by secondary literature that supports the findings of this article qualitativel.AbstrakSetiap orang percaya terpanggil untuk menjadi saksi Kristus dalam dunia ini. Dalam mengemban tugas itu orang percaya menghadapi situasi-situasi yang tidak mudah, ada tantangan dari dalam diri dan dari luar dirinya. Karena itu Tuhan telah memperlengkapi orang percaya dengan kuasa rohani yaitu Roh Kudus. Tindakan Allah di dalam Yesus Kristus mendasari seluruh perkembangan teologi Paulus dan orang-orang percaya, dalam keberadaan mereka di dalam Kristus, sambil membiarkan diri mereka ada dipimpin oleh Roh Kudus, juga berpartisipasi dalam status anakAllah,  Roh Kudus kemudian menjadi titik kunci dari realitas baru orang percaya. Makna kerajaan Allah sering kali dibahas oleh para hamba Tuhan yang mengungkapkan bahwa kerajaan Allah suatu hal yang akan datang atau sedang terjadi sekarang. Artikel ini memberi pemahaman bagi pembaca bahwa mengenal Kerajaan Allah adalah prioritas hidup orang percaya. Kerajaan Allah hanya dapat di ketahui, di kenal, dan di peroleh dengan mengenal Allah di dalam Kristus sebagai dasarnya. Penelitian ini menggunakan metode eksegesis dengan pendekatan analisis kata dari teks asli yaitu menemukan spiritual meaning dibalik teks asli. Artikel ini merupakan hasil penemuan empat lapisan makna eksegesis dari Roma 8:1-17dan didukung oleh literatur-literatur sekunder yang mendukung penemuan artikel ini secara kualitatif.